Tangerang Regency Government Policy on Waste Management at the Jatiwaringin TPA Tangerang - Ihwan Nudin (Trigin Publisher, 2020)
Residents whose economy is middle to upper class reject the existence of the Jatiwaringin TPA to continue to be in their environment. The existence of the Jatiwaringin TPA greatly disturbs the peace of the residents, especially Jatiwaringin Village, as well as several other villages, namely Buaranjati Village, Gintung Village, and Rajeg Mulya Village which are located in three sub-districts, because they are not far from the TPA area. Meanwhile, residents from the lower classes benefit from the presence of waste by managing and selling it. The Tangerang Regency Government has optimized the Jatiwaringin Final Disposal Site (TPA) in Mauk District as a place for waste disposal and processing in the area. So far, the 12-hectare TPA has only functioned as a waste disposal site. However, since 2011 the TPA has become a waste management site. Optimizing the Jatiwaringin TPA is a serious step for the government to handle waste, which is a demand for Law Number 18 of 2008 concerning Waste Management. The regulation states that each city/regency must process its own waste. So that the existence of the TPA can be accepted by all levels of society.